2007
DOI: 10.1371/journal.pone.0000413
|View full text |Cite
|
Sign up to set email alerts
|

Postcopulatory Sexual Selection Is Associated with Reduced Variation in Sperm Morphology

Abstract: BackgroundThe evolutionary role of postcopulatory sexual selection in shaping male reproductive traits, including sperm morphology, is well documented in several taxa. However, previous studies have focused almost exclusively on the influence of sperm competition on variation among species. In this study we tested the hypothesis that intraspecific variation in sperm morphology is driven by the level of postcopulatory sexual selection in passerine birds.Methodology/FindingsUsing two proxy measures of sperm comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
146
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(166 citation statements)
references
References 68 publications
17
146
2
Order By: Relevance
“…Our results are, however, comparable to what has been found in the red deer C. elaphus hispanicus (Malo et al 2006), where, although repeatability was statistically significant, within-male variance in total sperm length accounted for 43% of the total variance. These results also contradict theoretical developments predicting that postcopulatory sexual selection should result in stabilizing selection, disfavoring extreme sperm morphologies, and reducing variation in sperm size (Calhim et al 2007;Kleven et al 2009). The substantial within-male variance we found in house sparrows raises two questions: How is variance in sperm morphology maintained and has sperm morphology evolved toward a single optimum that maximizes male fertilization success?…”
Section: Discussioncontrasting
confidence: 65%
“…Our results are, however, comparable to what has been found in the red deer C. elaphus hispanicus (Malo et al 2006), where, although repeatability was statistically significant, within-male variance in total sperm length accounted for 43% of the total variance. These results also contradict theoretical developments predicting that postcopulatory sexual selection should result in stabilizing selection, disfavoring extreme sperm morphologies, and reducing variation in sperm size (Calhim et al 2007;Kleven et al 2009). The substantial within-male variance we found in house sparrows raises two questions: How is variance in sperm morphology maintained and has sperm morphology evolved toward a single optimum that maximizes male fertilization success?…”
Section: Discussioncontrasting
confidence: 65%
“…Links between reduced function, relaxed natural selection and greater variation has been acknowledged by more recent studies [19] and demonstrated to characterize certain vestigial traits of insects [20]. More distantly related but still relevant examples of reduced selection and increased variation include certain birds and fishes, which show greater sperm morphological variation coincident with a release of sexual selection [21,22]. In addition, reduced competition in Garter snakes may have increased variation heritability of colour patterns [23].…”
Section: Introductionmentioning
confidence: 99%
“…Again, an unequivocal, single explanation for this variation is lacking, although sperm size may have a function in post-copulatory sexual selection, including sperm competition, in at least some cases (e.g. Gage and Morrow, 2003;Calhim et al, 2007; for a review, see Pitnick et al, 2009).…”
Section: Introductionmentioning
confidence: 99%